Evaluating algorithms for an expertise recommender system - Uma Manikantan (2008)
This study evaluates two algorithms, Support Vector Machine and Bayesian Logistic Regression as applied to an Expertise Recommender System, and compares the results. The expertise area examined is academic research, the information being extracted from faculty web pages of universities world-wide. The study is aimed at the ability of distinguishing subject specialisations within a main subject.